The Compatibility of the Origin and Exception with the Purposes of Sharia in Fiqh Rulings of the Marriage - Al-Nimer, Nimer Mohammad (Dirasat: Shari'a and Law Sciences, 2021)
This research aims to show the importance of the purposes of Sharia in the context of Islamic law, which must be realized in all the original and exceptional provisions. This is done by stating what is meant by the original provision in the marriage provisions in the Islamic Sharia, stating what is meant by the exception provision in the marriage provisions in the Islamic Sharia, and stating the relationship between these two provisions. The nature of the topic tackled in this research necessitates the use of four approaches: an inductive method by tracking original and exceptional Fiqh provisions in marriage; a descriptive method by clarifying how these original and exceptional Fiqh provisions should be applied in practice; an analytical method to analyze these provisions; and finally a deductive method by confirming that these original and exceptional Fiqh provisions can fulfill the objectives of Sharia. The study has concluded that Sharia takes into account the general and the exceptional provisions, and in each of them, the Shariah objective is achieved. and that the effect of the general and exceptional provisions is to take into account the interest of the Muslims. All this is achieved in the general and exceptional provisions of marriage. The study also recommends that students of Science study the origin and exception in divorce rulings and other sections of fiqh and link them to purposes of Sharia..